From Social Infrastructure to Civic Center. The School as Laboratory of Collaborative Governance Models - Daniela Ciaffi; Emanuela Saporito; Ianira Vassallo (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the second half of the last century, after World War II, the Italian government defined an important period of public policies and projects to build a national welfare system in order to bridge the social and cultural gaps of a country with many different territorial situations. Half a century later, the complexification of the social and economic organization, which has transformed mass society into a plural society, has brought with it a multiplication and fragmentation of spatial and social needs for which the universal welfare system appears ineffective. The role of the public administration and its relationship to communities and the third sector have changed: increasingly often, alliances are defined to build projects that are closer to different social and cultural demands. This paper will focus on processes in which public service is enriched and regenerated by the care of reference communities: we seem to recognize the premises for a new way of administering public services, in which the public and the private collaborate on an equal level. We will adopt this perspective in observing what happens inside schools, which seems particularly interesting for at least two reasons. First of all, as the symbol of a public welfare service in crisis, it is simultaneously possible to recognize a certain habit of school communities taking part in the redevelopment of this service, through actions to care for the school building and its pertinent spaces. Secondly, the school also plays the role of a territorial actor, coming out of its own enclosures to take over urban space (that is, public gardens, parks, libraries, museums, cycle workshops, etc.) with educational projects at various levels. Turin represents an interesting case study, as a city where both public policies and social practices have integrated themselves, from education to urban regeneration, through institutional actors and local communities.